Determinación de los factores de riesgo para desarrollar cáncer de mama. - Barahona Viveros, Jean Lenin (2024)
Breast cancer is one of the most common cancers worldwide, and its incidence continues to rise. Therefore, identifying risk factors is essential for developing effective prevention and early detection strategies. This research analyzes the risk factors associated with breast cancer in the Ecuadorian female population to systematize prevention actions. In addition, the main risk factors documented in the scientific literature were categorized, the barriers and facilitators for the implementation of public health programs aimed at the prevention of breast cancer in Ecuador were also determined, and finally, evidence-based recommendations were proposed to improve prevention and early detection in the Ecuadorian context. The results indicate that age is the most frequently mentioned risk factor, with 14 citations, establishing it as a significant element in most of the studies analyzed. Obesity follows as the second most common risk factor, with 8 mentions, showing a strong correlation with breast cancer. Family history was cited 7 times, highlighting its importance in assessing risk. Other factors, such as alcohol consumption and hormonal contraception, received 3 mentions each, suggesting that they are also relevant, although less prevalent than age and obesity. Additional factors such as tobacco consumption, overweight, metabolic syndrome, late menopause, lifestyle, and occupational factors were mentioned less frequently but are still relevant. Less commonly cited factors include the BRCA1 and BRCA2 genes, breast changes, gynecological history, and genetic predisposition, suggesting that while they occur less frequently, they are still significant in the study of breast cancer. These findings are essential to adapt specific public health strategies for the prevention and early detection of breast cancer in Ecuador.